Aminoquinoline Schiff Bases as Non‐Acidic, Non‐Steroidal, Anti‐Inflammatory Agents. Issue 31 (2nd November 2017) - Bano, Bilquees; Khan, Khalid M.; Jabeen, Almas; Hameed, Abdul; Faheem, Aisha; Taha, Muhammad; Perveen, Shahnaz; Iqbal, Sarosh
Abstract: Inflammation is common localized condition which makes body reddened and swollen due to some injury or any infection. The commonly available drugs i. e. diclofenac, ibuprofen etc . in market against inflammation bear acid group which cause severe stomach disturbance in their prolong use. Thus, such issues required significant attention in term of introducing acid free new anti‐inflammatory agents with enhance efficacy. In the present study, we screened a series of eighteen aminoquinoline Schiff bases for their anti‐inflammatory activity. These compounds were tested for their inhibitory effect on intracellular reactive oxygen species (ROS) produced from phagocytes isolated from human whole blood. Among the synthetic analogs, ( E )‐4‐((quinolin‐5‐ylimino)methyl)benzene‐1, 2, 3‐triol (5 ), ( E )‐1‐(2, 4‐dimethoxyphenyl)‐ N ‐(quinolin‐5‐yl)methanimine (6 ), ( E )‐2, 6‐dimethoxy‐4‐((quinolin‐5‐ylimino)methyl)phenol (7 ), and ( E )‐4‐((quinolin‐3‐ylimino)methyl)benzene‐1, 2, 3‐triol (15 ) were found to exhibit potent activity with IC50 values of 1.9 ± 0.9, 2.7 ± 0.5, 1.4 ± 0.1, and 2.4 ± 0.1 μ g/mL, respectively. Ibuprofen with IC50 value of 2.5 ± 0.6 μ g/mL has been used standard in this assay. Cytotoxicity of these compounds was also tested against rat fibroblast cell line (3T3 cell line). The synthetic aminoquinoline Schiff bases were found to be non‐toxic in cellular model except trihydroxy derivative5 . The active compounds can serve as potential leads for new anti‐inflammatory drugs. Abstract : Aminoquinoline Schiff bases have been evaluated as anti‐inflammatory agents. Four compounds include ( E )‐4‐((quinolin‐5‐ylimino)methyl)benzene‐1, 2, 3‐triol (5 ), ( E )‐1‐(2, 4‐dimethoxyphenyl)‐ N ‐(quinolin‐5‐yl)methanimine (6 ), ( E )‐2, 6‐dimethoxy‐4‐((quinolin‐5‐ylimino)methyl)phenol (7 ), and ( E )‐4‐((quinolin‐3‐ylimino)methyl)benzene‐1, 2, 3‐triol (15 ) were exhibit potent activity with IC50 values between 1.4 ± 0.1 to 2.4 ± 0.1  μ g/mL, compare to Ibuprofen (IC50 = 2.5 ± 0.6  μ g/mL) These active compounds can be served as potential leads for new anti‐inflammatory drugs.